The Importance of Universal Values in Foreign Action Games (in the Case of German Action Games) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The significance of action games, the analysis of German action games, the inculcation of universal human values through the educational method and their introduction to Uzbek elementary school students through the experimental method are highlighted.